Propulsion System Issues in Hybrid Electric Vehicle - Wahsh, S.; Samir, E.; Hasan, M.; Wael, S. (ENCON 2013, 2013)
Hybrid Electric Vehicle (HEV) are the most promising alternatives to conventional Internal Combustion Engine Vehicle (ICEV) which satisfy increasing customer requirements such as fuel economy, ordinary road performance and drive-ability at minimum cost. This paper focusing on HEV performance of electrical system such as battery and electric motor drives. Mathematical models and simulation using MATLAB/SIMULINK is presented and implemented in a complete series–parallel HEV model from MATLAB/SIMULINK. Finally, simulation results are presented to demonstrate the effectiveness and applicability of the proposed system in the real-time implementation.